NILAI-NILAI PENDIDIKAN YANG TERDAPAT DALAM SURAT AL-INSAN AYAT 23-26 - A Adriantoni; Izzi Fekrat (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Tujuan dilakukan penelitian ini adalah untuk mengetahui nilai pendidikan akidah dalam surat al-Insan ayat 23-26, untuk mengetahui nilai pendidikan ibadah dalam surat al-Insan ayat 23-26, dan untuk mengetahui nilai pendidikan akhlak dalam surat al-Insan ayat 23-26. Penelitian ini merupakan penelitian kepustakaan (library research) yaitu serangkaian kegiatan yang berkenaan dengan metode pengumpulan data pustaka, membaca dan mencatat serta mengolah bahan penelitian yang ada di pustaka. Sumber data primer dari penelitian ini adalah tafsir al-Mishbah, tafsir ath-Thabari, tafsir al-azhar, tafsir al-Maraghi, Shafwatut Tafasir, dan tafsir Fi Zhilalil Quran karangan Sayyid Quthb. Sedangkan sumber data sekunder yang penulis gunakan dalam penelitian ini adalah buku asbabun nuzul dan buku-buku yang berkaitan dengan pendidikan Islam. Dalam mengkaji surat al-Insan ayat 23-26 ini penulis menggunakan metodologi penafsiran penidikan yaitu gabungan metode tahlily dan metode maudhu’i. Nilai–nilai pendidikan Islam yang terdapat dalam surat al-Insan ayat 23-26 adalah, pertama, nilai pendidikan akidah tentang beriman kepada al-Quran. Kaum muslimin wajib beriman kepada al-Quran. Karena al-Quran merupakan salah satu syiar ad-din yang menguatkan aqidah dan meresapkan keimanan. Kedua, nilai pendidikan ibadah tentang shalat lima waktu dan shalat tahajjud. Ketiga, nilai pendidikan akhlak tentang sabar dan istiqamah. Sifat sabar dan istiqamah merupakan sifat yang harus dimiliki oleh seseorang dalam kehidupan. The purpose of this study is to determine the value of Islamic education in the surah al-Insan verse 23-26, to determine the value of moral education in the surah al-Insan verse 23-26, and to determine the value of religious education in surah al-Insan verse 23-26 . This research is a research library (library research) is a series of activities related to the method of collecting data library, reading and recording and processing of research materials in the library. The primary data sources from this study are al-Mishbah's interpretation, Tafsir ath-Thabari, al-Azhar commentary, al-Maraghi commentary, Shafwatut Tafasir, and Qidb's Fi Zhilalil Quran commentary. While secondary data sources that the authors use in this study are books asbabun nuzul and books related to Islamic education. In reviewing the letter of al-Insan verse 23-26 is the author uses the method of interpretation of the investigation of the combined methods tahlily and maudhu'i method. The values of Islamic education contained in the letter al-Insan verse 23-26 is, first, the value of faith education to believe in the Qur'an. The Muslims must believe in the Qur'an. Because al-Quran is one of the ad-din syiar which strengthens the aqidah and absorbs the faith. Second, the value of worship education about the five daily prayers and tahajjud prayers. Third, the moral education value of patience and istiqamah. The nature of patience and istiqamah is a trait that must be possessed by someone in life.